2014
DOI: 10.1016/j.egypro.2014.12.318
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Perception for Demand Response among Residential Consumers

Abstract: Smart Grids are often seen as an enabler for an electricity market with increased benefits for both consumers and environment. From a system level perspective, many advantages could be achieved by implementing these innovative technologies. Furthermore, implementing smart metering could give consumers possibilities to obtain a better understanding of their own electricity consumption. The information could also help consumers to react on price signals by adjusting their consumption patterns. Increased knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The cost of energy is argued to be a key motivator for the uptake of new and innovative energy technologies for the home and many argue that financial incentives are the most important motivators for people to change their behaviour, and respond to DR programming and flexibility requirements [40,86]. This is also evident in our results, showing that environmental motivations are also important for respondents, corresponding with findings on residents in general in relation to non-economic factors increasingly reported in the literature as a determinant in people's motivation for DR uptake [46,87]. However, previous studies on TOU have also highlighted the limitations of economic motivations alone [44,45], especially for higher income groups or those that do not use electricity for space heating and cooling [88].…”
Section: Discussionsupporting
confidence: 86%
“…The cost of energy is argued to be a key motivator for the uptake of new and innovative energy technologies for the home and many argue that financial incentives are the most important motivators for people to change their behaviour, and respond to DR programming and flexibility requirements [40,86]. This is also evident in our results, showing that environmental motivations are also important for respondents, corresponding with findings on residents in general in relation to non-economic factors increasingly reported in the literature as a determinant in people's motivation for DR uptake [46,87]. However, previous studies on TOU have also highlighted the limitations of economic motivations alone [44,45], especially for higher income groups or those that do not use electricity for space heating and cooling [88].…”
Section: Discussionsupporting
confidence: 86%
“…The review identified a wide range of motivations for residential consumers to participate in demand response. Financial and environmental benefits were the most common motivations identified, and of these, financial benefits were typically given the highest importance (AECOM, 2011;Allcott, 2011;Dütschke and Paetz, 2013;Carmichael et al, 2014;Torstensson and Wallin, 2014;US DOE, 2016). More specifically, some users state that bill reductions are more appealing than rewards or other financial incentives (Buchanan et al, 2016), although there may be little difference in actual enrolment rates for critical peak pricing and critical peak rebates (US DOE, 2016).…”
Section: Results: Consumer Motivations For Demand Responsementioning
confidence: 99%
“…This increases the cost of demand-response-ready investments, makes the measurements difficult to obtain and, consequently, reduces the economic impact of demand response. Furthermore, the perception of demand response among residential consumers is not always positive [23]. Some of the household devices with a high potential for demand response include clothes washers and dryers, air conditioners, water heaters, ovens, dishwashers and refrigerators [24].…”
Section: Flexible Consumersmentioning
confidence: 99%